Identification of LMO2 as a new marker for acinic cell carcinoma of salivary gland - Dong Sheng; Yan Zhang; Tian Xue; Xiao-Yan Zhou; Xiao-Qiu Li (BMC, 2022)
Abstract Background The distinction between acinic cell carcinoma (ACC) and secretory carcinoma (SC) of the salivary gland is hampered by the lack of specific diagnostic markers. It is known the cytoplasm of glandular cells in the salivary gland immunohistochemically expresses LIM Domain Only 2 (LMO2). Herein, we aim to evaluate the expression status of LMO2 in a large cohort of tumors of the salivary gland, with an emphasis on its significance in the distinction of ACC and SC. Methods Immunohistochemical stains were performed to evaluate the expression of LMO2 in normal tissues and tumors of salivary gland. Results LMO2 was expressed in normal serous acinar cells of the salivary gland. We also found the cytoplasmic immunostaining of LMO2 was specific and sensitive for the recognition of ACCs including those with morphological overlaps with SCs, whereas the cytoplasmic expression of LMO2 was not detected in SCs. Conclusions LMO2 is useful for the recognition of ACC and is of potential value in distinguishing ACC from SC.